Experimental Investigation of the Machining Characteristics in Graphite-Powder-Mixed Electrochemical Discharge Machining of Microholes in Glass - Weidong Tang; Jikai Yao; Jize Zhang; Quancai Zhao; Lixiang Fan; Cong Mao; Xiaoming Kang; Xuyu Li; Shuhan Chen (Micromachines, 2023)
The effect of graphite powder on the machining characteristics in graphite-powder-mixed electrochemical discharge machining of microholes was still not clear. How the discharge mechanism changed with the addition of graphite powder into the electrolyte, which further led to changes in the morphology of the machined holes, remained to be revealed. In this study, a series of microhole machining experiments were conducted in glass. Comparisons of the discharge energy, microhole entrance diameter, hole taper, and tool electrode morphology after machining were made when machining in the electrolytes with and without graphite powder. Experimental results revealed that there were a lot of small pulse currents distributed on the current waveform when machining with the graphite-powder-mixed electrolyte. The average discharge energy of the small pulse current was 2.8 times as much as that of the general electrochemical discharge. After introducing graphite powder into the electrolyte, the entrance diameter of the hole became larger when the hole depth was deeper than 200 μm. The HAZ width increased with increasing hole depth at the voltage of 37–41 V, while it decreased at the voltage of 43 V. A reduction in hole taper angle with a range of 0.5° to 2.3° was achieved. In addition, after machining in electrolytes with and without graphite powder, the tool electrode surfaces showed different morphologies due to different discharges.